Studi Numerik Pendinginan Udara Pada Kandang Sapi Kapal Ternak Menggunakan CFD (Computational Fluid Dynamic) - Puruhitno Pambudi Rohimawan; Agus Setiawan Priyo; Endri Kusuma George (Proceedings Conference on Marine Engineering and its Application, 2018)
Livestock vessels are used to distribute and transport livestock from one place to another. Similar research has been carried out by making cattle models in the beams which are considered to make air distribution less evenly. This research will be carried out simulation use 3D cattle’s model. This simulation aims to determine the distribution of air temperature, air velocity, air pressure and air flow patterns uses a CFD (computational fluid dynamic) simulation method. Based on the simulation result, the average of air temperature distribution is 300oK or 27oC at cattle pen A and B. The average of air velocity distribution is 0,669 m/s at cattle pen A and 0,7 m/s at cattle pen B. The average of air pressure distribution is 0,211 pa at cattle pen A and -0,267 pa at cattle pen B and the airflow pattern is around a model of cattle. The distribution of air temperature at 300oK or 27oC by RH (relative humidity) 70%-90%, THI (Temperature Humidity Index) shows in the alert condition between 75 – 78. So, The cattle pen A and B have not good the comfort zone and make a cattle to be mild stress. Because of it, the air temperature has to be down by adding a cooling instrument.